JUNIOR HIGH SCHOOL STUDENTS’ ABILITY TO APPLY ALGEBRA IN REAL-WORLD PROBLEMS - Agasi, Georgius Rocki; Wahyuono, Yakobus Dwi; Rudhito, Marcellius Andy (International Journal of Indonesian Education and Teaching (IJIET), 2017)
In accordance with the 2013 curriculum that uses Scientific Approach where students learn using the 7M method (Observing, Questioning, Trying, Gathering Information, Reasoning, Concluding, and Communicating), the real problem is a tool which is considered fairly important to be used in learning. Mathematical modeling is an approach in which students bring real problems into mathematical problems. Algebra is an important tool used in modeling a real problem into a mathematical problem. Students are asked to observe the environment around them and then asked to make their mathematical model in an algebraic form. The subjects in this study were 21 eighth-grade students of Pangudi Luhur Junior High School in Srumbung, Magelang, Central Java, Indonesia. This research uses Qualitative Approach. The result of this study found that most students are able to create algebraic forms from the environment they have observed, but there are still difficulties. Some groups still need quite a lot of help from teachers but some also need a little help from teachers.